Botticelli : artist and designer - Debenedetti, Ana (Renaissance lives., 2021)
A revealing look at the commercial strategy and diverse output of this canonical Renaissance artist. In this vivid account, Ana Debenedetti reexamines the life and work of Renaissance artist Sandro Botticelli through a novel lens: his business acumen. Focusing on the organization of Botticelli's workshop and the commercial strategies he devised to make his way in Florence's very competitive art market, Debenedetti looks with fresh eyes at the remarkable career and output of this pivotal artist within the wider context of Florentine society and culture. Uniquely, Debenedetti evaluates Botticelli's celebrated works, like The Birth of Venus, alongside less familiar forms such as tapestry and embroidery, showing the breadth of the artist's oeuvre and his talent as a designer across media.